Can the Demonstration Method via YouTube Improve the Mathematics Learning Outcomes of Grade V Students? - Sri Ruhul Hayati; Diana Amelia; Husnul Wahidah; Achmad Saleh; Estikomah Estikomah; Nanang Sugiarto (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The lack of skills of educators in using varied teaching methods causes low learning outcomes and a lack of active student involvement in understanding spatial and volume material in Mathematics lessons. This research aims to investigate the effect of using the demonstration method via YouTube on the Mathematics learning outcomes of class V students regarding geometric shapes and volumes. This research uses the classroom action research (PTK) method. It is hoped that the use of YouTube as an interesting and easily accessible learning media source can help students understand Mathematics concepts. The participants in this research were 25 class V students. Based on the results of quantitative data analysis, it was found that students' grades increased in each cycle. In the pre-cycle, 68% of students completed. Meanwhile, in cycle 1, 72% of students completed. Then in cycle 2 students completed 100%. From the results of these data, it can be concluded that there has been an increase in students' Mathematics learning outcomes in space and volume material using the demonstration method via YouTube Video Media.